Minimizing an Electron Flow to Molecular Oxygen in Photosynthetic Electron Transfer Chain: An Evolutionary View - Kozuleva, Marina A.; Ivanov, Boris N.; Vetoshkina, Daria V.; Borisova-Mubarakshina, Maria M. (Frontiers in Plant Science, 2020)
Recruitment of H2O as the final donor of electrons to light-governed reactions in photosynthesis has been an utmost breakthrough bursting the evolution of life and leading to accumulation of O2 molecules in atmosphere. O2 molecule has a great potential to accept electrons from the components of the photosynthetic electron transfer chain (so-called the Mehler reaction). The present review provides a synopsis of the Mehler reaction mechanisms specifying the changes in the structure of the photosynthetic electron transfer chain of oxygenic phototrophs that probably had occurred as the result of evolutionary pressure to minimize the electron flow to O2. These changes are warranted by the fact that the efficient electron flow to O2 would decrease the quantum yield of photosynthesis. Moreover, the reduction of O2 leads to reactive oxygen species, namely the superoxide anion radical and hydrogen peroxide, which cause oxidative stress to plants cells if they are accumulated in a significant amount. From another side, hydrogen peroxide acts as a signaling molecule. We particularly zoom into the role of photosystem I and the plastoquinone pool in the Mehler reaction.